The Soong sisters - Cheung, Yuen-Ting; Law, Alex; Ng, See Yuen (Solar Films, 1996)
A biographical account of the three Soong sisters, Ai-ling, Ching-ling, and Mei-ling, who became Mrs. H. H. Kung, Mme. Sun Yat-sen, and Mme Chiang Kai-shek, respectively. Set in China, it starts at Sun Yat-sen's rise to power, to his death, to Chiang Kai-shek's rise to power, to the Japanese invasion, to the end of Chiang Kai-shek's reign, and the establishment of Taiwan, and shows how the sisters helped shape modern China's history.